2013
DOI: 10.1149/05011.0071ecst
|View full text |Cite
|
Sign up to set email alerts
|

An Arrhenius Argument to Explain Electrical Conductivity Maxima versus Temperature

Abstract: The existence of conductivity maxima in pure molten salt was interpreted by Grantham and Yosim to be due to ion association at low densities. Tödheide used a chloride-transfer shifting-equilibrium hypothesis to explain ion association in the case of bismuth trichloride. We have performed density-functional-theory based molecular dynamics simulations of the molten chlorides of Bi(III), Sn(II), and Hg(II), and Tödheide's hypothesis is not supported. Instead, the simulations imply a hopping barrier for ions betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…With the observation in simulation of a Grotthuss relay of Br − ions in the molecular liquid HgBr 2 , we now suggest that the "hopping" ideas we proposed earlier 23,24 be recast as density-dependent aspects of a general Grotthuss conductivity mechanism for all ions. A comparison with previous literature discussion of the Grotthuss mechanism of H + in aqueous media is then apt.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…With the observation in simulation of a Grotthuss relay of Br − ions in the molecular liquid HgBr 2 , we now suggest that the "hopping" ideas we proposed earlier 23,24 be recast as density-dependent aspects of a general Grotthuss conductivity mechanism for all ions. A comparison with previous literature discussion of the Grotthuss mechanism of H + in aqueous media is then apt.…”
Section: Discussionmentioning
confidence: 52%
“…2,[17][18][19][20][21][22] However, we reported in 2012 the results of ab initio molecular dynamics (AIMD) simulations which showed that molten BiCl 3 is a network liquid with very little molecular character, and instead put forward a new theory to explain the conductivity maximum vs temperature. 23,24 The new theory attributed conductivity to atomic ions "hop[ping] from counterion to counterion," and used a density-dependent Arrhenius equation to ascribe the maximum to the competing effects of rising hopping opportunities (rising frequency factor A with thermal expansion) and diminishing hopping probability per opportunity (due to rising activation energy E a as the hopping distance increases with thermal expansion):…”
Section: Introductionmentioning
confidence: 99%